Advances in Toll-like receptor biology: Modes of activation by diverse stimuli. (3rd September 2015) - Bryant, Clare E.; Gay, Nick J.; Heymans, Stephane; Sacre, Sandra; Schaefer, Liliana; Midwood, Kim S.
Abstract: As we learn more about the biology of the Toll-like receptors (TLRs), a wide range of molecules that can activate this fascinating family of pattern recognition receptors emerges. In addition to conserved pathogenic components, endogenous danger signals created upon tissue damage are also sensed by TLRs. Detection of these types of stimuli results in TLR mediated inflammation that is vital to fight pathogenic invasion and drive tissue repair. Aberrant activation of TLRs by pathogenic and endogenous ligands has also been linked with the pathogenesis of an increasing number of infectious and autoimmune diseases, respectively. Most recently, allergen activation of TLRs has also been described, creating a third broad class of TLR stimulus that has helped to shed light on the pathogenesis of allergic disease. To date, microbial activation of TLRs remains best characterized. Each member of the TLR family senses a specific subset of pathogenic ligands, pathogen associated molecular patterns (PAMPS), and a wealth of structural and biochemical data continues to reveal the molecular mechanisms of TLR activation by PAMPs, and to demonstrate how receptor specificity is achieved. In contrast, the mechanisms by which endogenous molecules and allergens activate TLRs remain much more mysterious. Here, we provide an overview of our current knowledge of how very diverse stimuli activate the same TLRs and the structural basis of these modes of immunity.